PENUNDAAN PENGESAHAN PERDAMAIAN DALAM PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG OLEH HAKIM DIKAITKAN DENGAN ASAS KEPASTIAN HUKUM - Agitha Putri Andany Hidayat Agitha; Anita Afriana (Jurnal Poros Hukum Padjadjaran, 2021)
ABSTRAKPerdamaian dalam PKPU menawarkan cara-cara pembayaran seluruh atau sebagian utangnya sebagai upaya menghindari kepailitan, sehingga perdamaian berlaku secara hukum dan mengikat para pihak diperlukan pengesahan perdamaian dari Pengadilan Niaga. Namun dalam praktik, ditemukan adanya penundaan pengesahan perdamaian yang telah disetujui para pihak akibat laporan yang belum diserahkan Pengurus dalam masa PKPU. Penulisan artikel ini bersifat deskriptif analitis, dengan tujuan untuk melihat penundaan pelaksanaan pengesahan perdamaian dalam PKPU oleh Hakim di Pengadilan Niaga dan akibat hukum atas penundaan pengesahan perdamaian tersebut serta kaitannya dengan asas kepastian hukum. Hasil menunjukkan bahwa pelaksanaan pengesahan perdamaian dalam Penundaan Kewajiban Pembayaran Utang diawali dengan pemungutan suara (voting) para kreditor dan memperoleh kekuatan hukum tetap melalui putusan pengesahan perdamaian oleh Pengadilan Niaga. Menurut UUKPKPU penundaan pengesahan perdamaian Pengadilan Niaga dapat dilakukan dengan mengundurkan dan menetapkan tanggal sidang yang harus diselenggarakan paling lambat 14 (empat belas) hari sejak penundaan tersebut. Ketentuan yang mengatur jangka waktu ini merupakan substansi formil, hukum acara Kepailitan dan PKPU yang tidak dapat dikesampingkan hakim, mengikat, dan memberikan kepastian hukum bagi para pihak. Penundaan pengesahan perdamaian dalam PKPU berakibat penyelesaian utang debitor kepada kreditor menjadi tertunda, sebab perjanjian perdamaian belum berlaku secara hukum dan mengikat para pihak. Pengesahan perdamaian yang menyimpangi Pasal 284 ayat (3) UUKPKPU, mengakibatkan perdamaian tidak sah dan debitor dinyatakan pailit.Kata kunci: kepastian hukum; pengesahan; perdamaian; PKPU. ABSTRACTThe reconciliations in PKPU (Debt Payment Obligation Postponement) offers full or half of the debt payment methods in order to avoid bankruptcy, the reconciliation are legally applied and binding the parties needed for reconciliation validation from the Commercial court. Yet in practice, there found indications of reconciliation’s approval delay which has been approved by the parties as the result of reports that has yet to submitted to the committee in the time of PKPU meanwhile by the judge with the verdict of time extention in the form of PKPU still deviate from the legislation, so that it leads to the validity of the reconciliation. This articles is decriptive analytical, with the purpose to see the the delay in impelementation validation in PKPU by the judge in Commercial Court and the legal consequences of the said reconciliation’s aproval delay and its relation to the principle of legal certainty. This research found that the implementation of the ratification reconciliation in PKPU begins with a vote of the creditors and obtains permanent legal force through the decision of ratification reconciliation by the Commercial Court. According to the UUKPKPU, the postponement of the ratification of the reconciliation of the Commercial Court may postpone and set a trial date no later than 14 (fourteen) days after the postponement. The provisions governing this period of time are formal substance, the procedural law of Bankruptcy and PKPU which cannot be overruled by judges, bind, and provide legal certainty for the parties. Delaying the ratification of the reconciliation in the PKPU resulted in the settlement of debtor’s debt to creditors to be delayed, because the reconciliation had not been legally enforce and binding on the parties. The ratification reconciliation that violates Article 284 paragraph (3) of the UUKPKPU, results in the reconciliation being invalid and the debtor being declared bankrupt.Keywords: legal certainty; PKPU; reconciliation; validation.